The Benefits of Vaccination against SARS-CoV-2 during Pregnancy in Favor of the Mother/Newborn Dyad - Daniela-Eugenia Popescu; Cosmin Cîtu; Ana Maria Cristina Jura; Nicoleta Lungu; Dan Navolan; Marius Craina; Alin Semenescu; Florin Gorun; Mihai-Andrei Jura; Valerica Belengeanu; Marioara Boia (Vaccines, 2022)
When the first vaccines against SARS-CoV-2 emerged, pregnant women were excluded from clinical trials, so vaccine recommendations were initially adjourned, with late initiation for this populational category. The present study aims to quantify the serum and breastmilk values of SARS-CoV-2 spike protein antibodies in both the mother and her newborn after complete vaccination during pregnancy. Ninety-one vaccinated patients were included, some of whom presented COVID-19 infection during pregnancy. In the delivery room, venous blood was collected from the mother and umbilical cord blood from her offspring. All samples were processed using the ECLIA (electrochemiluminescence) method. Breastmilk was collected and tested during the third postnatal day. The highest maternal serum values were 19,523 U/mL (detection limit > 0.8 U/mL) and in breastmilk, 206.7 U/mL. Every single newborn had antibody values higher than 0, with a mean serum value (M = 5288.37, SD = 5661.49) significantly higher than 0, t(90) = 8.91, p < 0.001. Consequently, this study intents to emphasize the importance of vaccination against SARS-CoV-2 during pregnancy. This double kind of neonatal protection, attained by placental and breastmilk transfer, can be accomplished by encouraging vaccination, breastfeeding, bonding, and providing maternal empowerment to participate in her infant’s care.